BNB-BnNn Nano-Motor in Binding with ACC (tRNA) Nucleotides as an Amino Acid Detector in Ribosome: QM/MM & Monte Carlo Studies - (:unkn) unknown (AMG Transcend Association, 2022)
The electromagnetic non-bonded interactions of BNB molecule inside the BnNn (such as B12N12, B15N15, and B18N18) ring as a detector for tRNA-Amino acid conjugation has been investigated by QM/MM & Monte Carlo methods. In this study, we have shown that the BNB-BnNn systems can work as a nano rotor-stator for detecting tRNA during the tRNA-Amino-acid conjugation. We have employed the B12N12-tRNA (glu), B12N12–tRNA(phe) and B12N12-BNB-tRNA(arg) systems coupled with BN (-, 0, +) B inside the B12N12 ring (as a rotor) (n=12, 15, 18). We have shown that the tRNA as an extrinsic factor (stator) is set in the BNB- B12N12 system due to the generation of radical, anion, and cation forms of BN(-,0,+)B. We have also calculated the tRNA-BNB-B12N12 and obtained quantized transitional frequencies among the forms of radical, anionic, and cationic. The three frequencies have been yielded as νr-c ) 486948.498 GHz, νa-c ) 1792900.812 GHz, and νr-a ) 2507076.816 GHz. It can be seen that all observed frequencies appeared in the IR and macro wave regions.